No Change, No Life? What We Know about Phase Variation in Staphylococcus aureus - Vishal Gor; Ryosuke L. Ohniwa; Kazuya Morikawa (Microorganisms, 2021)
Phase variation (PV) is a well-known phenomenon of high-frequency reversible gene-expression switching. PV arises from genetic and epigenetic mechanisms and confers a range of benefits to bacteria, constituting both an innate immune strategy to infection from bacteriophages as well as an adaptation strategy within an infected host. PV has been well-characterized in numerous bacterial species; however, there is limited direct evidence of PV in the human opportunistic pathogen Staphylococcus aureus. This review provides an overview of the mechanisms that generate PV and focuses on earlier and recent findings of PV in S. aureus, with a brief look at the future of the field.